Pemberian Ekstrak Daun Kelor terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri Putus Sekolah Usia 12 – 18 Tahun - Yulianti Anwar; Veni Hadju; Samrichar R; Andi Alimuddin Unde; Andi Nilawati Usman; Ni Luh Putu Herli Mastuti (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Teenage girls are prospective mothers who will give birth to the nation's next generation. Anemia among teenage girls causes the risk of giving birth to low birth weight babies (LBW) so that it has an impact on the optimal quality of life (bleeding, infection, abortion, low birth weight, premature, and defects congenital). Moringa leaves contain high amounts of vitamin A, vitamin C, vitamin B, calcium, potassium, iron, and protein which are easily digested and assimilated by the human body. Moringa oleifera based supplements have an impact on pregnant women and prevent adverse pregnancy outcomes. The purpose of this study was to determine the effect of Moringa leaves extract on increasing hemoglobin levels in teenage girls who drop out of school. This quantitative research was true experimental with the design used was the Randomized Controlled Double-Blind Pre-Posttest by looking after 2 months intervention of giving Moringa leaves extract to teenage girls dropping out of school. The sample criteria used based on the inclusion criteria were obtained as many as 30 teenage girls who dropped out of school which was divided into 15 interventions or given extract moringa leaves a dose of 2x1 with a content of 1000 mg and 15 controls or given TTD with a dose of 2x1 with a content of 1000 mg. The analysis used univariate analysis and bivariate analysis. Then the data collected in this study was processed analytically with a Paired T-test and Independent T-Test. The results showed the difference in hemoglobin levels between the intervention group (p = 0.000) and the control group(p = 0.011). The feeding of Moringa leaves extract capsules had the effect of increasing hemoglobin levels after 2 months of intervention.